2020
DOI: 10.1016/j.mehy.2020.110018
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to use Proton Pump Inhibitors in COVID-19 treatment and prophylaxis?

Abstract: Coronaviruses (CoV), discovered after 1960, caused human life-threatening outbreaks. SARS-CoV2, which appeared in Wuhan, China in December 2019, causing Severe Acute Respiratory Syndrome and has different features than other coronaviruses, has been determined and the disease caused by the virus has been called “Coronavirus Disease-2019” (COVID-19). This disease activates both the natural and acquired immune system. The cytokin storm, in which blood levels of proinflammatory cytokines are detected excessively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
0
18
1
1
Order By: Relevance
“…In our cohort, those who died had a significantly higher use of NSAIDs (10% vs. 3.84%, p=0.024) and statins (42.2% vs. 30.4%, p=0.035). Many studies have reported PPI [28,29] use as a risk factor, and although our data show a similar trend, it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 97%
“…In our cohort, those who died had a significantly higher use of NSAIDs (10% vs. 3.84%, p=0.024) and statins (42.2% vs. 30.4%, p=0.035). Many studies have reported PPI [28,29] use as a risk factor, and although our data show a similar trend, it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 97%
“…Although the possibilities of considering PPIs as therapeutic options in COVID-19 have been proposed and discussed in some of the recent publications [45,51,52], the clinical evidence for the same is a mix bag. We have hypothesized their potential roles based on specific cellular mechanisms and summarized all the relevant findings and information till date to get a well-balanced and holistic view on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…However, current use of PPIs conferred a 79% higher risk of severe clinical outcomes following SARS-CoV-2 infection. In contrast, Taştemur and Ataseven 138 hypothesised that PPI may be used for treatment and prophylaxis of COVID-19, owing to their anti-inflammatory, antioxidant, immunomodulatory and antifibrotic properties.…”
Section: Gi Side Effects Of Medications Used For Covid-19mentioning
confidence: 99%